Cardiac PDK4 promotes neutrophilic PFKL methylation and drives the innate immune response in diabetic myocardial infarction - Song Yang; Longxin Yan; Lang Chen; Gaijuan Su; Long Yang; Lili Gong; Lihong Liu (Pharmacological Research)
NETosis plays a pivotal role in the innate immune response after diabetic myocardial infarction (MI), exerting a profound influence on the overall pathological process and potential recovery outcomes. The metabolism of diabetic cardiomyocyte actively creates a specialized micro environment for the innate immune response after MI. However, the mechanism by which cardiac metabolism drives NETosis remains unclear. Utilizing public databases of human MI sc-RNA datasets, we discovered that cardiomyocyte PDK4 expression mediates the intensification of glycolysis, which is strongly correlated with NETosis. Through mass spectrometry imaging and phenotype assessment, we ascertained that specific knockout of PDK4 in cardiomyocytes (PDK4fl/flMyh6Cre, male, 6 weeks) led to a reduction in NETosis by restraining micro environmental lactate (LA) production. In addition, the role of LA in promoting NETosis has been further corroborated by in vivo/in vitro experiments involving LA supplementation and its absence. Moreover, LA redirects neutrophil metabolic flux from glycolysis to the pentose-phosphate pathway (PPP). Mechanistically, LA triggers metabolic remodeling through the PRMT9-mediated methylation of PFKL at the R301 residue, resulting in PFKL inactivation and the consequent restriction of glycolysis. Our findings reveal the crucial role of cardiomyocyte metabolism in NETosis, shedding light on the role of LA as a vital signaling molecule in the crosstalk between cardiomyocytes and neutrophils. Importantly, we screened pitavastatin, a potential inhibitor of PDK4 among the FDA-approved drugs, and verified that it can alleviate NETosis in diabetic MI, which provides a rationale for drug selection in diabetic MI patients.